Nickel-Catalyzed Decarbonylation of α-Oxyacetic Acid Thioesters: Hydroxymethylation of Mercaptans - Tian, Rui; Li, Jia-Xin; Zhu, Yong-Ming (Synlett, 2023)
A strategy for the Ni-catalyzed decarbonylation of α-oxyacetic acid thioesters is described, providing a new pathway for the synthesis of monosulfide acetals, and further proving that oxygen atoms can stabilize an α-carbocation and promote a decarbonylation reaction. This method has good functional-group compatibility and can tolerate a wide range of electron-withdrawing, electron-neutral, and electron-donating substituents. In addition, this method complements the conventional cross-coupling reactions.
Keywords: decarbonylation; rearrangement; nickel catalysis; C–S bond; monothioacetals